Characteristics of Low-Income Able-Bodied Adults Without Dependents: Implications for Public Policy. Issue 2 (3rd April 2017) - Lim, Younghee; Mitchell, Katherine Stamps
ABSTRACT: This article provides descriptive information about contemporary able-bodied adults without dependents (ABAWDs) using 2008 Current Population Survey data. Analyses of the demographic, employment, economic, and skill-building characteristics of ABAWDS reveal that poor ABAWDs struggle with low rates of program receipt and continuous employment as well as low levels of education in addition to other persistent disadvantages. Results suggest that this group has specific needs that can be addressed by social policies aimed at improving access to education, skill-building training, and long-term employment.